Reflecting upon the concept of anonymity - Frois, Catarina (2010)
Starting from an analysis of the uses of anonymity in 12 Step associations — namely as an instrument used by members to manage personal information, both in relationships with other members as well as non-members — this article aims to extend the results of this study to different contexts where anonymity is resorted to, identifying its uses and characteristics at a broader level, as a mediator of social relationships.